Association analysis identifies new risk loci for non-obstructive azoospermia in Chinese men. - Hu, Z.; Li, Z.; Yu, J.; Tong, C.; Lin, Y.; Guo, X.; Lu, F.; Dong, J.; Xia, Y.; Wen, Y.; Wu, H.; Li, H.; et al. (Nature communications, 2014)
Male factor infertility affects one-sixth of couples worldwide, and non-obstructive azoospermia (NOA) is one of the most severe forms. Our previous genome-wide association study (GWAS) identified three susceptibility loci for NOA in Han Chinese men. Here we test promising associations in an extended three-stage validation using 3,608 NOA cases and 5,909 controls to identify additional risk loci. We find strong evidence of three NOA susceptibility loci (P<5.0 × 10(-8)) at 6p21.32 (rs7194, P=3.76 × 10(-19)), 10q25.3 (rs7099208, P=6.41 × 10(-14)) and 6p12.2 (rs13206743, P=3.69 × 10(-8)), as well as one locus approaching genome-wide significance at 1q42.13 (rs3000811, P=7.26 × 10(-8)). In addition, we investigate the phenotypic effect of the related gene (gek, orthologous to CDC42BPA) at 1q42.13 on male fertility using a Drosophila model. These results advance our understanding of the genetic susceptibility to NOA and provide insights into its pathogenic mechanism.